Factorial Structure and Validity of the Quantified Behavior Test Plus (Qb+©). (December 2017) - Hirsch, Oliver; Christiansen, Hanna
This study investigates the factorial structure and validity of the Quantified Behavior Test Plus (Qb+©), a computerized test to objectively evaluate the three attention deficit/hyperactivity disorder core symptoms, hyperactivity, inattention, and impulsivity, independently. Confirmatory and exploratory factor analyses were conducted with an outpatient sample of 773 subjects ≥12 years old. In a second sample of 297 patients ≥16 years, a multitrait–multimethod analysis was performed to examine concurrent and discriminant validity. The discriminative power of the Qb+ was investigated using a general linear model and logistic regression analysis. The three factorial structure (Hyperactivity, Inattention, Impulsivity) was verified in the confirmatory factor analysis. Fit indices demonstrated a good model fit and factor loadings were almost all moderate to high. In the multitrait–multimethod analysis, the criterion for convergent validity was fulfilled. The discriminant validity of the Qb+ was partially supported. Significant but small gender and age effects were found. In the logistic regression analysis, omission errors and reaction time variability, belonging to the Inattention factor, were able to discriminate between subjects with and without attention deficit/hyperactivity disorder. The internal structure of the Qb+ was verified. Its validity was partially supported. Results regarding discriminative power were mixed.